Thermal enhancement in a solar air heater channel using rectangular winglet vortex generators - Depaiwa, Nattawoot; Chompookham, Teerapat; Promvonge, Pongjet (My University, 2010)
The forced convection heat transfer and friction loss behaviors for turbulent airflow through a constant heat flux channel solar air heater with rectangular winglet vortex generator (WVG) are experimentally investigated in this work. The rectangular winglet pairs are considered with two different arrangements by pointing upstream (PU) and pointing downstream (PD) of the flow. Ten pairs of the WVGs with various attack angles (a) of 60°, 45° and 30° are mounted on the test duct entrance wall to create longitudinal vortex flows over the tested channel. Measurements are carried out for the rectangular channel air heater of aspect ratio, AR = 10 and height, H = 30 mm with the WVG height, b/H = 0.4 and a transverse pitch ratio, P/H = 1. The flow rate is in terms of Reynolds numbers based on the inlet hydraulic diameter of the channel ranging from 5000 to 23,000. The experimental results show that the solar air heater channel with rectangular WVG provides significantly higher heat transfer rate and friction loss than the smooth wall channel. The use of larger attack angle value leads to higher heat transfer rate and friction loss than that of lower one. The PD-WVGs performs higher heat transfer rate and friction loss than the PU one for similar operating conditions. In comparison, the largest attack angle (α= 60°) of the PDWVGs yields the highest increase in Nusselt number and friction factor while the lowest attack angle (α = 30°) of the PU-WVGs shows the best thermal performance.
Keywords: Channel; Enhanced heat transfer; Longitudinal vortex generator; Winglet